Audiologic Evaluation of Patients with Mucopolysaccharidosis at a Pediatric Hospital - Gomes, Ariana Braga; Pereira, Rodrigo Guimarães; Vassoler, Tríssia Maria Farah; Alcantara, Lauro João Lobo; Zimmermann, Elise; Santos, Mara Lúcia Schmitz Ferreira (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Mucopolysaccharidosis are characterized by the deficit of lysosomal enzymes corrupting the glycosaminoglycans. Accumulating these metabolites causes several alterations, such as otologic alterations.Objective: To evaluate a number of patients with mucopolysaccharidosis at Pequeno Principe Hospital, emphasizing their audiologic alterations and establish a permanent evaluation protocol for these patients.Method: A backward-looking study of audiologic evaluation by using records of 18 patients diagnosed with mucopolysaccharidosis and attended at Pequeno Principe Hospital between January 2005 and November 2010.Results: 7 records were selected, out of which only one did not have a hearing loss, and most of them presented conductive or mixed hearing loss, and only one had an exclusively sensorineural loss. Six of these patients had also been submitted to at least one otorhinolaryngological procedure.Conclusion: Mucopolysaccharidosis patients require a permanent care and a multidisciplinary follow-up. The pediatric otorhinolaryngologist plays an important role when performing the otologic and audiologic evaluation and managing the airways, since almost all the patients evaluated presented some kind of hearing loss and an indication of otorhinolaryngologic procedure. The pattern determined in our service was at least an initial consultation when there is a suspicion and/or diagnosis of MPS and sequential consultations that were at least twice a year or more frequent, if necessary.
Keywords: otorhinolaryngology; pediatrics; mucopolysaccharidosis; audiology